2010
DOI: 10.1159/000318493
|View full text |Cite
|
Sign up to set email alerts
|

Experience from the Argentine Pegvisomant Observational Study: Preliminary Data

Abstract: The GH receptor antagonist pegvisomant is an efficient agent to achieve biochemical control of acromegaly in those cases refractory to surgery and medical therapy with somatostatin analogs. We conducted an observational multicenter study consisting of data collection in accordance with the standard management of patients with acromegaly in everyday practice. We reviewed the medical records of 28 patients, 23 females, who were treated with pegvisomant due to the lack of biochemical response or intolerance to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…The lack of data concerning radiotherapy is a limit of our study. On the other hand, it is note of worthy that 72 % of patients in group B achieved normal IGF-1 levels at the last visit, a figure perfectly in line with other clinical studies [8][9][10][11][12]. On the contrary, only 57 % of group A showed disease control at last visit, a disappointing result probably justified by an inadequate patients' selection, by insufficient pegvisomant doses or by the enrollment in group A of younger patients with a more aggressive disease.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The lack of data concerning radiotherapy is a limit of our study. On the other hand, it is note of worthy that 72 % of patients in group B achieved normal IGF-1 levels at the last visit, a figure perfectly in line with other clinical studies [8][9][10][11][12]. On the contrary, only 57 % of group A showed disease control at last visit, a disappointing result probably justified by an inadequate patients' selection, by insufficient pegvisomant doses or by the enrollment in group A of younger patients with a more aggressive disease.…”
Section: Discussionsupporting
confidence: 86%
“…Drug effectiveness varies widely from one study to another, ranging 59-100 % [3][4][5][6][7][8][9][10][11]. Inadequate dose titration, poor compliance to daily injections, suboptimal selection of patients, and some problems related to IGF-1 measurement could justify a lowerthan-expected efficacy although this phenomenon has neither been appropriately investigated nor well explained until now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 A discrepancy exists between the proportion of patients achieving normal IGF-I levels during treatment with pegvisomant in randomized controlled trials and community-based databases, suggesting differences in participant selection, dose titration, patient compliance, history of earlier irradiation, and occurrence of adverse events (LQ). 33,[35][36][37] If long-term control of acromegaly is achieved with pegvisomant, down-titration of the dose or decreasing the frequency of administration might be possible (DR).…”
Section: Dopamine Agonistmentioning
confidence: 99%
“…Accordingly, PEG starting dose should be higher and dose titration more rapid in younger patients, in the obese subjects and in those with a worse endocrine profile [31, 32]. Previous studies also showed that IGF-I normalization requires lower doses in male than in female patients, and in irradiated compared to non-irradiated cases [17, 26, 33]. On the other hand, an appropriate PEG dose titration up to the maximum allowed dosage was shown to normalize IGF-I levels in up to 90% of cases, even in the real life setting [34].…”
Section: Biochemical Outcomementioning
confidence: 99%